Production of an Anise- and Woodruff-like Aroma by Monokaryotic Strains of Pleurotus sapidus Grown on Citrus Side Streams - Friederike Bürger; Maximilian Koch; Marco A. Fraatz; Alejandra B. Omarini; Ralf G. Berger; Holger Zorn (Molecules, 2022)
The production of natural flavors by means of microorganisms is of great interest for the food and flavor industry, and by-products of the agro-industry are particularly suitable as substrates. In the present study, Citrus side streams were fermented using monokaryotic strains of the fungus Pleurotus sapidus. Some of the cultures exhibited a pleasant smell, reminiscent of woodruff and anise, as well as herbaceous notes. To evaluate the composition of the overall aroma, liquid/liquid extracts of submerged cultures of a selected monokaryon were prepared, and the volatiles were isolated via solvent-assisted flavor evaporation. Aroma extract dilution analyses revealed p-anisaldehyde (sweetish, anisic- and woodruff-like) with a flavor dilution factor of 218 as a character impact compound. The coconut-like, herbaceous, and sweetish smelling acyloin identified as (2S)-hydroxy-1-(4-methoxyphenyl)-1-propanone also contributed to the overall aroma and was described as an aroma-active substance with an odor threshold in air of 0.2 ng L−1 to 2.4 ng L−1 for the first time. Supplementation of the culture medium with isotopically substituted l-tyrosine elucidated this phenolic amino acid as precursor of p-anisaldehyde as well as of (2S)-hydroxy-1-(4-methoxyphenyl)-1-propanone. Chiral analysis via HPLC revealed an enantiomeric excess of 97% for the isolated product produced by P. sapidus.